What's in a Smile? Politicizing Disability through Selfies and Affect. Issue 1 (5th December 2018) - Yadlin-Segal, Aya
Abstract: This article focuses on selfies and empowerment of individuals with physical disabilities. By exploring the #FSHDselfies campaign as a case study, I discuss the role affect plays in mediated advocacy for the representation of non-normative bodies, allowing disabled individuals to gather as a community and disrupt contemporary beauty standards. I draw on the case study to re-articulate the term "community of affect" (Climo, 2001) as the socio-political structure that promotes marginalized groups' negotiation of collective identity and communal action geared towards cultural, social, and political change. This community can be seen as a sub-section or a specific discursive space categorized under "affective publics" (Papacharissi, 2014). I show in this context how participatory forms of representation open a space for negotiation and criticism of marginalized groups on the one hand, while oversimplifying the complex and diverse lives of minority groups on the other hand.